Spontaneous nongenetic variation of group size creates cheater-free groups of social microbes. (24th January 2018) - Amherd, Michaela; Velicer, Gregory J; Rendueles, Olaya
Abstract : Social microbes are exposed to cheaters that exploit the advantages of cooperative actions without paying their fair share. Upon starvation, myxobacterial cells cooperatively aggregate into discrete fruiting bodies containing stress-resistant spores. Fruiting bodies formed from a genetically identical population can vary greatly in the number of spores that they carry. We show that such variation allows the exclusion of cheaters from some fruiting bodies and can be a mechanism to maintain cooperation. Abstract: In social organisms, cheaters that gain a fitness advantage by defecting from the costs of cooperation reduce the average level of cooperation in a population. Such cheating load can be severe enough to cause local extinction events when cooperation is necessary for survival, but can also mediate group-level selection against cheaters across spatially structured groups that vary in cheater frequency. In cheater-laden populations, such variation could be generated by the formation of new homogeneous groups by small numbers of identical cells. Here, we use the model social bacterium Myxococcus xanthus to test whether population bottlenecks inherent to the starvation-induced formation of multicellular fruiting bodies can generate cheater-free groups within an initially cheater-laden population. We first show that genetically identical fruiting bodies vary greatly in their numbers of stress-resistant spores. We further show mathematically and experimentally that this variation can include small cheater-free groups. Such nongenetic variation in group size was found to occur in a variety of M. xanthus isolates and Myxococcus species. Our results suggest that stress-induced reductions in group size may serve as a general process that repeatedly purges genetic diversity from a minority of social groups, thus recurrently generating high-relatedness social environments unburdened by cheating load.